Effect of Binders and Pressures on Physical Quality of Some Biomass Briquettes - Wakchaure, G C; Mani, Indra (Journal of Agricultural Engineering, 2009)
The effects of biomass materials, different organic binders with varying concentrations and applied die pressures on the physical characteristics of biomass briquettes were studied. Three biomass materials (mustard stalk, mixed waste of tree leaves and grasses in 3:1 proportion and wood waste) along with three organic binding materials (molasses, press mud and distillers dry grain) with varying concentration of 5, 10, 15 and 20% were used for preparation of briquettes. The briquettes were formed at three die pressures of 123.42 MPa, 117.68 MPa and 112.34 MPa, and their relevant physical properties were determined. Press mud was found a better binding agent, followed by distillers dry grain and molasses. The physical characteristics like moisture content, bulk density, compression ratio and compressive strength desired for better utilization and safe handling and transportation were found to be best for briquettes made from press mud and mustard stalk at die pressure of 123.42 MPa.